The manifestation of native language transfer in ESL learning / Mah Boon Yih - Mah, Boon Yih (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2009)
English language has always been a perceived problem for Chinese ESL learners particularly on syntactical rules in sentence construction. However, not many studies have been conducted with a specific focus on the interlanguage of Chinese ESL learners. This study is primarily concerned about how the learner's existing linguistic knowledge influences the course of English language development among Chinese ESL learners. This constitutes a suitable starting point to focus on the similarities and differences of learners' language patterns to their target language as it may be one of the possible results of the manifestation of learners' native language transfer. The study of first language (LI) transfer involves the study of errors (negative transfer), avoidance of target language forms, and their overuse (overgeneralization).